The possibility of coriander seed disinfection with essential oil of peppermint - Mikić, Sara (Journal of Agricultural Sciences (Belgrade), 2021)
Testing seed health has a goal to ensure a healthy crop and to prevent the spread of plant diseases by trade and exchange of seeds. The need to study and apply essential oils and plants extracts to protect the seeds is growing and becoming more important. Coriander (Coriandrum sativum L.) is an annual herbaceous, aromatic, spicy and medicinal plant from the Apiaceae family, known for its seeds that have characteristic and pleasant odour. In human medicine, coriander is a part of various medicines for the treatment of digestive organs. Phytopathogenic fungi and bacteria are the most common and significant causes of coriander seed disease. The aim of this study was to assess coriander seed health and to investigate the possibility of seed disinfection using peppermint (Mentha x piperita) essential oil. The health of the seeds was examined by the filter paper method. For seed disinfection different concentrations (1, 2, 5 and 10%) of peppermint essential oil were used. The composition of the essential oil was determined by gas chromatographic analysis. The results of seed health analysis showed presence of a fungus after seven days of incubation in a humid chamber at room temperature. The fungus was identified as Alternaria sp. based on the symptoms, and macroscopic and microscopic features of the fungus (on seed and potato dextrose agar). Immersion treatment of infected seed in peppermint essential oil reduce presence of Alternaria sp. on coriander seeds. The results of this study show the possibility of disinfecting coriander seeds with peppermint essential oil in order to reduce infection with Alternaria sp.